1998
DOI: 10.1046/j.1526-100x.1998.06408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Acidity on Aquatic Insects in Rocky Littoral Habitats of Lakes Near Sudbur y, Ontario

Abstract: Benthic aquatic insects were collected from rocky nearshore areas ( Ͻ 1 m deep) of 17 lakes near Sudbury, Ontario, with a pH range of 4.7-7.3 and a size range of less than 10 ha to over 10,000 ha. These insect communities were composed of taxa common to lake softsediments and streams. Direct and indirect effects of lake acidity appeared to be major controls on the structure of these communities, implying that several factors may be involved in restructuring during acidification or recovery. Declines in abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Post and Cucin (1984) showed that predation pressure on littoral benthic invertebrates by introduced yellow perch decreased biomass and body size in benthic invertebrate communities. Many other studies have shown the important interactions between fish and littoral benthic invertebrate communities (Diehl 1992, Carbone et al 1998, Sherwood et al 2002. Fish can be efficient predators and are important in structuring invertebrate communities in aquatic ecosystems ranging from streams (Wooster 1994, Nilsson et al 2008) to tropical reefs (Ayal andSafriel 1982, Dulvy et al 2004).…”
Section: What Is the Role Of Time And Water Chemistry In Biological Rmentioning
confidence: 99%
“…Post and Cucin (1984) showed that predation pressure on littoral benthic invertebrates by introduced yellow perch decreased biomass and body size in benthic invertebrate communities. Many other studies have shown the important interactions between fish and littoral benthic invertebrate communities (Diehl 1992, Carbone et al 1998, Sherwood et al 2002. Fish can be efficient predators and are important in structuring invertebrate communities in aquatic ecosystems ranging from streams (Wooster 1994, Nilsson et al 2008) to tropical reefs (Ayal andSafriel 1982, Dulvy et al 2004).…”
Section: What Is the Role Of Time And Water Chemistry In Biological Rmentioning
confidence: 99%
“…In Jasne Lake, there were also relatively numerous taxa such as: Procladius sp., Ablabesmyia monilis, Cladopelma lateralis and Dicrotendipes sp. These taxa in significant densities also in acidic Canadian (Dermott et al, 1986;Carbone et al, 1998) and American lakes (Dougherty & Morgan, 1991) were found.…”
Section: Discussionmentioning
confidence: 81%
“…These organisms are also commonly found in other acid water bodies due to their resistance to low water pH (Carbone et al, 1998). The cited authors, studying the Canadian lakes, significantly higher densities of this group of animals in acidotrophic than in neutral lakes have noted.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations